Educational change - Tracey Carlyon; Christopher Branson (New Zealand Journal of Teachers' Work)
Despite the availability of an abundant amount of guiding literature, only about 30% of planned educational changes are successful. Clearly there is something essential missing from our understanding of how to successfully lead educational change. A review of the literature provides an awareness that success is far more likely if the leader pays as much attention to the needs of those who are bringing about the change as they do to the elements of the planned change strategy. Arguably, however, this still maintains a top-down perspective of the change process. Hence the departure point of this article is its presentation of a change process from the perspective of those explicitly affected—that is, a view from the ‘bottom up’. Specifically, this article presents and discusses both quantitative and qualitative data from research conducted in Aotearoa New Zealand involving primary school teachers who changed the class levels in which they taught. It seeks to provide a unique contribution to the development of successful educational change strategies by presenting the teachers’ views about the most effective leadership practices during times of change.